Transcriptomic responses to shifts in light and nitrogen in two congeneric diatom species - Ma, Xiao; Qin, Zhen; Johnson, Kevin B.; Sweat, L. Holly; Dai, Sheng; Li, Gang; Li, Chaolun (Frontiers in Microbiology, 2024)
Light and nitrogen availability are basic requirements for photosynthesis. Changing in light intensity and nitrogen concentration may require adaptive physiological and life process changes in phytoplankton cells. Our previous study demonstrated that two Thalassiosira species exhibited respectively distinctive physiological responses to light and nitrogen stresses. Transcriptomic analyses were employed to investigate the mechanisms behind the different physiological responses observed in two diatom species of the genus Thalassiosira. The results indicate that the congeneric species are different in their cellular responses to the same shifting light and nitrogen conditions.When conditions changed to high light with low nitrate (HLLN), the large-celled T. punctigera was photodamaged. Thus, the photosynthesis pathway and carbon fixation related genes were significantly down-regulated. In contrast, the small-celled T. pseudonana sacrificed cellular processes, especially amino acid metabolisms, to overcome the photodamage. When changing to high light with high nitrate (HLHN) conditions, the additional nitrogen appeared to compensate for the photodamage in the large-celled T. punctigera, with the tricarboxylic acid cycle (TCA cycle) and carbon fixation significantly boosted. Consequently, the growth rate of T. punctigera increased, which suggest that the larger-celled species is adapted for forming poststorm algal blooms. The impact of high light stress on the small-celled T. pseudonana was not mitigated by elevated nitrate levels, and photodamage persisted.